Are we overlooking Natura 2000 sites? Lessons learned from a transnational project in the Adriatic Sea - Gianni, Fabrizio; Manea, Elisabetta; Cataletto, Bruno; Pugnetti, Alessandra; Bergami, Caterina; Bongiorni, Lucia; Pleslić, Grgur; Vilibić, Ivica; Bandelj, Vinko (Frontiers in Marine Science, 2022)
Since the adoption of the Habitats and Birds Directives by EU governments, marine Natura 2000 (N2K) sites have been established in the European Mediterranean Sea, creating one of the largest international networks of protected areas. Nevertheless, to date, marine N2K sites are generally scarcely implemented, studied and monitored, and thus their management effectiveness is weak, and their environmental status is often unknown. The Interreg Italy-Croatia ECOSS project aimed at establishing the ECOlogical observing system of the Adriatic Sea (ECOAdS), to integrate the existing research and monitoring activities in the area, and to promote data sharing at international level, for enhancing monitoring and conservation in Adriatic N2K network. In the framework of ECOSS, a conceptual model was developed and applied to selected N2K sites, to review the existing knowledge, assess site effectiveness, and suggest possible improvements in their monitoring and management based on the contribution that ECOAdS can provide to their implementation. Information on social, ecological, and oceanographic elements related to the conservation and management of these case studies was gathered by consulting the project partners involved in the management and monitoring of the sites and through a literature review. The results of this study revealed a discouraging condition with no management plan in most of the sites, while regulatory measures are generally in place but without surveillance. Monitoring activities are performed occasionally, and information on presence and status of protected species is often lacking or outdated. Although the N2K network provides a unique opportunity to advance marine conservation and achieve the 30% conservation target by 2030, the biggest challenge ahead is the proper management and monitoring of N2K sites. The proposed conceptual model may be taken as a framework to properly set up ecological observing systems in the N2K network and help overcome current limitations, integrating scientific research within the N2K conservation strategies.